Navigating the Borderlands: System-Impacted Latina Girls, Cultural Tyranny, and the Juvenile Legal System - Lopez, Vera (Journal of contemporary criminal justice, 2025)
This study explores the experiences of eight system-impacted Latina girls through interviews, using Anzaldúa’s borderlands framework as a theoretical lens to examine how they navigate cultural expectations of gender and sexuality within their families and the juvenile legal system. These young women resist oppressive norms, challenging white hegemonic feminism and traditional gender roles. Their perceived “transgressions”—speaking out about sexual victimization, defying heteronormativity, and engaging in premarital sex—invite punishment rather than support. This study advocates for trauma-informed, community-based programs rooted in Chicana feminisms, emphasizing art, storytelling, and intergenerational healing to foster resistance and collective healing beyond punitive measures.